INTEGRATIVE TECHNOLOGIES OF TREATMENT PROCESS OPTIMIZATION SUR EXERSICE ORGANISATION WORK OF DEPARNAMENT RADIOTHERAPIE STATE ESTABLISHMENT «KHARKIV S. P. GRIGORIEV FOR MEDICAL RADIOLOGY OF THE NATIONAL ACADEMY OF MEDICAL SCIENCES OF UKRAINE» - Starenkiy, V. P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The possibilities of up-to-date information technologies use as a means of integrative optimization processes of the radiation treatment preparation and carrying out are analyzed.The justification of principles of radiotherapy department organizational and technical modernization related to the installation of innovative treatment equipment is performed. The new factors of improving the quality of radiation treatment due to the application of integrative information technology are identified for example radiotherapy department State Establishment «Kharkiv S. P. Grigoriev Institute for Medical Radiology of the National Academy of Medical Sciences of Ukraine».